Peran Serta Hukum Dalam Perlindungan Hak Kekayaan Intelektual Atas Penggunaan Logo Dari Internet Untuk Tujuan Komersial - Muhammad Raffi Raihan Jauhari; Rani Apriani (Peneliti.net, 2022)
As regulated by the 1945 Constitution, the fulfillment of protection, guarantee, and legal certainty by individuals and groups in self-development, namely the discovery of an intellectual property, guaranteed continuity and originality by the State. Under Indonesian law, it is still often found that some irresponsible individuals and groups / individuals, abuse of Intellectual Property Rights, one of which is the use of the Logo without rights, permits, and illegally from the Internet for commercial purposes. The urgency of protection is carried out on the basis that in a work, creation, or innovation found by individuals or groups it has an economic right and moral right, more than that, the benefits of Intellectual Property can be used by the community and also to support the ideals of the nation and the Republic of Indonesia. Indonesia will be a progress and prosperity of a nation. As mentioned above, the state, in this case, is obliged to take all legal aspects to protect the personal reputation of individuals and groups.